Hands-On Cybersecurity for Finance : Identify vulnerabilities and secure your financial services from security breaches /: Identify vulnerabilities and secure your financial services from security breaches. (2019) - Dr, Ozkaya, Erdal; Aslaner, Milad
No abstract available